Raised shorelines and deglaciation of the Loch Long/Loch Fyne area, Western Scotland - Sutherland, Donald G. (The University of Edinburgh, 1981)
The objective of the research reported in this thesis was to elucidate the mode of disappearance of the last ice-sheet to cover the Loch Long/Loch Fyne area in the SW Highlands, and to establish the sequence of raised shorelines that has been formed as a result of the interplay between eustatic and isostatically-induced sea-level changes consequent upon the melting of the ice. The study was geomorphological in orientation and a methodology was adopted that involved mapping, at a scale of 1:10,560, all glacial, fluvial and marine landforms below approx. 75 - 100 m O.D., and the subsequent accurate instrumental surveying of all relevant landforms. A certain amount of mapping back from the coast was also carried out where relevant. The errors inherent in the methods adopted and in the use of various types of marine landforms were quantitatively assessed and it was concluded that raised shorelines could be reconstructed with an accuracy of ±0.54 m using intertidal deltas and ±0.61 m using marine erosional features. The southern part of the study area was deglaciated first at ca. 13,000 yr BP. The dominant mode of deglaciation was that of rapid retreat in the sea lochs (possibly as much as 500 m/yr) due to calving that left isolated dead-ice masses in various side valleys. This retreat was punctuated by two major periods of stillstand or readvance, the Otter Ferry Stage (ca. 12,900 ± 200 yr BP) and the Loch Lomond Readvance (ca. 11,000 - 10,000 yr BP). Eight raised shorelines have been identified as having formed during the relative fall of sea-level from ca. 38 - 40 m O.D. that accompanied the disappearance of the icesheet. A particularly well developed shoreline, CLG2, was formed during the Otter Ferry Stage. A further unique rock-cut shoreline, the Main Rock Platform, was at least in part formed during the cold conditions immediately prior to and during the Loch Lomond Stadial. During the Loch Lomond Stadial glaciers extended down Loch Long to near Ardentinny and down Loch Fyne to beyond Furnace. The mountains in ...